Effect of Section Thickness on the Microstructure and Hardness of Ductile Cast Iron - Guzel, Erdogdu; Yuksel, Caglar; Bayrak, Yahya; Sen, Ozkan; Ekerim, Ahmet (CARL HANSER VERLAG, 2014)
Ductile cast irons have several engineering and manufacturing advantages compared to other cast materials such as steels. These include high damping capacity, wear resistance, to and lower manufacturing cost. The combination of good mechanical properties and casting abilities of ductile cast iron makes its usage successful in structural applications especially in the energy and automotive industries. In this study, the influence of the section thickness on the microstructure and hardness of spheroidal graphite cast iron was investigated with a cascaded model using the full mold casting method. By the high linear correlation coefficient, R-2 > 0.90, it was observed that the section thickness directly affected the microstructure and hardness. An increase in the cross-sectional thickness decreases hardness and number of graphite nodules per square millimeters, however, percentage of ferrite was increased.
Keywords: Materials testing; ductile iron; section size; microstructure; hardness; GRAPHITE; Materials Science